Yuck's slime monster : and, Yuck's gross party - Morgan, Matthew (Yuck, 2012)
In "Yuck's Slime Monster," the Prince of Pungency hatches a disgusting plan--if he can't bring his pet slug to school, he'll bring a Slime Monster instead! Soon enough, there's goo and slop everywhere! Can Yuck control the Slime Monster before it takes over his school? And in "Yuck's Gross Party," Yuck's sister Polly--prim as a Princess--throws a birthday bash that doesn't include him. So to get even, he assembles his revolting gang for a gruesome party with gross games galore! And he and his pals are going to make Polly the most disgusting birthday cake ever!